Macroeconomic Management and Financial Stability: The Implications for East Asia - Chinn, Menzie D. (My University, 2004)
The determinants of economic and financial linkages between developed and developing countries, with special focus on East Asia, are explored. The paper discusses recent efforts to reform the international financial architecture, and the conclusion discusses prospects for adjustment in light of the empirical relationships identified.